An Exploration of Measurement Invariance across Sex in Intimate Partner Violence Perpetration. Issue 2 (17th February 2022) - Wareham, Jennifer; Wagers, Shelly M.; Rodriguez, Lindsey M.; Neighbors, Clayton
ABSTRACT: The present study examines the assumption of measurement invariance across sex from two instruments of intimate partner violence (IPV) perpetration. Data were used from two studies of self-reported IPV perpetration among adult college students. Study 1 employs a subset of the Revised Conflict Tactics Scale (CTS2) for 901 young adult females and males. Study 2 employs a subset of the Safe Dates scale for 599 young adult females and males. Multiple-group confirmatory factor analysis was estimated in a forward, sequential process to test measurement invariance of IPV perpetration across sex. Both studies indicated multiple items violated the assumption of measurement invariance across sex for the latent IPV perpetration constructs. Findings revealed the IPV perpetration scales suffered from sex-bias for certain IPV behavior items. Future research should explore sources of variance in IPV perpetration scales and their impact on key correlates.